Interest of Confirmation Tests in the Diagnosis of Viral Hepatitis C to Blood Donors in Abidjan-Côte d'Ivoire - Yassongui, Mamadou Sekongo; Saydou, Kabore; Bamory, Dembele; Kouadio.Daniel, Yao; Liliane, Bogui-Siransy; Jean, Luc Adjoumani; Agba, Abisse; Seidou, Konaté (Journal of Hematology and Oncology Research, 2020)
Introduction The anti-HCV RIBA test verifies the presence of anti-HCV serum antibodies detected by the Elisa test. In Côte d'Ivoire, screening for hepatitis C is done exclusively by enzyme immunoassays. In order to reduce the number of HCV positive blood donor exclusions on ELISA, we conducted this study which aimed to demonstrate the value of the RIBA test in confirming diagnosis of viral hepatitis C to blood donors. Methods Our study, which took place from 02 to 23 February 2008 in the laboratory of Abidjan NBTC, focused on 200 sera of blood donors anti-HCV positive (Elisa test) selected according to the ratio. The DECISCAN HCV PLUS confirmation test of BIORAD was used. Results Among the 200 HCV samples positive by EIA, 49% (98/200) were confirmed positive. RIBA gave an indeterminate result in 40% of cases (80/200); and negative in 11% of cases (22/200) corresponding to false ELISA devices. In RIBA 96 samples had a low ELISA ratio of which 21% (20/96) were RIBA negative, and 79% (76/96) were indeterminate. RIBA positive samples (98/200) had a high ratio in 82% of cases (80/98). The presence of NS3 (C33) and NS4 (C100) was noted in 100% of cases (98/98, C2 in 37% (36/98) of cases and C1 in 18% of cases (18/98). RIBA indeterminate noted the presence of NS3 in 98% of cases (78/80) and NS4 in 30% of cases (24/80). Proteins C1, C2 and NS4 are essential for the diagnosis of confirmation of viral hepatitis C by RIBA. Conclusion These results attest to the lower specificity of enzyme immunoassays (ELISAs); hence the benefit of using RIBA confirmatory tests. A significant number of donors are excluded from blood donation in Côte d'Ivoire on the basis of false positive results obtained by the ELISA technique.
Keywords: Confirmatory test - Hepatitis C - Blood donors